Memacu Pertumbuhan Ekonomi Di Propinsi Jawa Tengah Melalui Peningkatan Kunjungan Wisatawan Dengan Jumlah Hotel Dan Pendapatan Asli Daerah Sebagai Variabel Intervening - Srisinto Srisinto (STIE AUB Surakarta, 2018)
The purpose of this study was to analyze the effect of the number of tourists on economic growth with the number of hotels and local revenue (PAD) as intermediate or intervening variables in Central Java Province. In theory, the number of tourists influences PAD through the variable number of hotels, while the number of tourists and the number of hotels influences economic growth through PAD, for this reason the path analysis method is used in this study. The data used in this study came from the Central Statistics Agency (BPS), namely the number of tourists, the number of hotels, local revenue (PAD) and gross regional domestic product (GDP) on the basis of constant prices in 2010. The results showed that i) the amount tourists and the number of hotels simultaneously had a positive and significant effect on local revenue (PAD) ii) the number of tourists, the number of hotels and local revenue (PAD) simultaneously had a positive effect on economic growth. By referring to the results of these studies, as well as to increase PAD in Central Java province, efforts are needed from the local government and stakeholders to try to improve the facilities and facilities and infrastructure related to tourism activities. In this study the intervening variable in the form of the number of hotels, needs to be considered as an effort to increase local revenue (PAD) in the Central Java province.Keywords: Number of tourists, Number of hotels, Regional Original Income (PAD) and Economic Growth.